Calves gastrointestinal nematodes and Eimeria prevalence and associated risk factors in dairy farms, southern Ethiopia - Maireg Hailu; Kassahun Asmare; Endrias Zewdu Gebremedhin; Vincenzo Di Marco Lo Presti; Maria Vitale; Desie Sheferaw (East African Journal of Biophysical and Computational Sciences)
Erratum to: Calves gastrointestinal nematodes and Eimeria prevalence and associated risk factors in dairy farms, southern Ethiopia Maireg Hailu1, Kassahun Asmare2, Endrias Zewdu Gebremedhin3, Vincenzo Di Marco Lo Presti4, Maria Vitale4, Desie Sheferaw2